Does Instrumentation of the Fractured Level in Thoracolumbar Fixation Affect the Functional and Radiological Outcome?. Issue 1 (January 2023) - Mohammed, Riaz; Carrasco, Roberto; Verma, Rajat; Siddique, Irfan; Mohammad, Saeed; Elmalky, Mahmoud
Study Design: Retrospective comparative study. Objectives: To compare radiological and functional outcomes of patients with fixation constructs utilizing pedicle screw stabilization at the fracture level (FL group) versus patients with non-fracture level (NFL group) fixation in single level fractures of the thoracolumbar junction (T11-L1). Methods: 53 patients of whom fracture level screw was used in 34 (FL group) were compared to 19 patients in NFL group. Radiological parameters analyzed were sagittal index, bi-segmental kyphosis (Cobb) angle and degree of vertebral height restoration. Prospectively collected patient reported functional outcomes and post-operative complications were also studied. Stepwise regression analysis adjusted by age, gender and functional scores was performed to account for the small numbers and unequal sizes of the groups. Results: Back pain score was significantly lower in the FL group ( P < 0.025). Core Outcome Measures Index scores and leg pain scores, though low in the FL group, were not statistically significant. The regression analysis showed that the inclusion of the fracture-level screw was independently associated with a greater change in sagittal index and vertebral height restoration post-operatively. Sagittal index was maintained through to final follow up as well. The bi-segmental Cobb's angle correction was not associated with fracture-level screw construct. There was no significant difference between the groups for revision surgery, deep infection, implant failure or length of hospital stay. Conclusion: The inclusion of the fracture-level pedicle screws in the fixation construct significantly improves the immediate and final measured radiological parameters, with improved functional scores in single level unstable vertebral fractures of the thoracolumbar junction.